25th January: 3rd Sunday after the Epiphany: Mark 1:14-20 - Knights, Chris H. ca. 196? (The expository times, 2014)
The article presents a Bible reflection on the Book of Mark about the followers of Jesus. Topics highlighted include the importance of repenting and believing in the good news of God, sacrifice showed by the disciples of Jesus to follow him, challenges that people may experience when they give their life and follow Jesus.